Middle Ordovician (middle Darriwilian) Archaeospicularia and Entactinaria (radiolarians) from the Table Cove Formation, Piccadilly Quarry, Newfoundland, Canada. (September 2021) - Kachovich, Sarah; Aitchison, Jonathan C.
Abstract: New, distinctive, well-preserved and previously undescribed constituents of a Middle Ordovician (middle Darriwilian, Dw2) radiolarian assemblage from the Table Cove Formation in Newfoundland are described. Three-dimensional X-ray micro-computed tomography (μ-CT) facilitates detailed examination of key specimens revealing hitherto unknown details of the internal morphologies of key lower Paleozoic taxonomic groups, among which a lack of knowledge has previously impeded resolution of higher taxonomic rankings. Twenty-seven archaeospiculid and entactinarian taxa are described and illustrated including six new species: Westernbrookia polygonata n. sp., Neopalaeospiculum piccadilliensis n. sp., Ramuspiculum laxum n. sp. Spongentactinia nazarovi n. sp., Aspiculum irregulare n. sp., and Nyfrieslandia ramosissima n. sp. The investigation extends the known ranges of the species: Pararcheoentactinia reedae Won and Iams, 2002 ; Sphaeroentactinia robusta Won and Iams, 2015 ; Varispiculum ectospiculatum Won and Iams, 2015 ; and Svalbardospiculum multifurcatum (Won, Iams, and Reed, 2005 ), together with the genus Echidnina to the mid-Darriwilian. UUID: http://zoobank.org/74826b7b-bb86-45d5-ad23-e6e65e0706df .